Inguinal Hernia in Infant - Matthew A Kumaat; Harsali Lampus; Nathaniel Pali (Universitas Sam Ratulangi, 2022)
Abstract: Inguinal hernia in infant is a condition of protrusion of the intestinal organs due to thepatency of processus vaginalis. The ratio of incidence between male and female infants isapproximately 8:1. The incidence of inguinal hernia ranges from 1-5% in children and full-terminfants, whereas in premature infants there is a significant increase in the number, which is around30%. Clinical manifestations that can occur in infants with inguinal hernias are the appearance ofa lump when straining, crying, coughing, or sneezing, patient could look restless because of thepain and discomfort. The diagnosis of inguinal hernia can be made by history taking, physicalexamination, and supporting examination. Management of inguinal hernia is by surgery, can bean open herniotomy or laparoscopy.Keywords: inguinal hernia; infantÂ Abstrak: Hernia inguinalis pada bayi merupakan kondisi penonjolan organ intestinal akibatadanya patensi prosesus vaginalis. Perbandingan rasio kejadian antara anak laki-laki dan perempuankurang lebih sekitar 8:1. Insidensi hernia inguinalis berkisar 1-5% pada anak dan bayi cukupbulan, sedangkan pada bayi prematur terdapat kenaikan angka yang bermakna yaitu sekitar 30%.Manifestasi klinis yang dapat terjadi pada anak dengan hernia inguinalis adalah timbulnyabenjolan pada saat mengedan, menangis, batuk, atau bersin, anak terlihat gelisah karena nyeri danrasa tidak nyaman. Penegakan diagnosis hernia inguinalis dapat dilakukan dengan anamnesis,pemeriksaan fisik, dan pemeriksaan penunjang. Tatalaksana hernia inguinalis ialah denganherniotomi terbuka atau laparoskopi.Kata kunci: hernia inguinalis; bayi